Determinación de elementos micronutrientes y tóxicos en alimentos de la población infantil de Lima metropolitana: Parte I: determinación mediante análisis por activación neutrónica instrumental de Ca, Cl, K, Mg y N a en muestras de leche y preparaciones de leche con cereal, consumidos por la población infantil en edad de destete - Montoya, Eduardo (1993)
The contents of Ca, Cl, K, Mg and Na, in milk and milk with cereal, consumed by the peruvian children were determined by short irradiation INNA using RP-10 reactor, with a thermal flux of 10 13 ncm-2 s-1, and a pneumatical system. The comparative mcthod with solutions of primary standards of each element determined was used. The IAEA-A11-milk powder, IAEA-H4-Animal muscle and IAEA-V10-Hay powder, reference materials were periodically analyzed, together with the samples, in order to check the quality of analytical results.